KLL Dielectronic Recombination of Highly Charged Sulfur and Silicon Ions. (21st May 2014) - Ali, Safdar
Abstract : Dielectronic recombination measurements for highly charged ions were performed at the Stockholm refrigerated electron beam ion trap. We have obtained KLL DR resonance strengths for highly charged H- and He-like sulfur and silicon ions. The experimental results are compared with the theoretical data obtained from GRASP II code. Both the experimental and calculated results agree well within the experimental error bars. Moreover, the dielectronic recombination resonance strengths are used to obtain the new scaling parameters by incorporating our results with the previous measurements and to check the behaviour of scaling formula for H- and He-like isoelectronic sequences.